AN ANALYSIS OF LINGUISTIC FEATURES IN THE SPEECHES OF BUSINESS COMMUNITY - Wienny Ardriyati (Universitas Stikubank (UNISBANK) Semarang, 2012)
This research is about an analysis of linguistic features in the speeches of business community which are about the speech of Indonesian President. It is found out that the themes are expressing the remarkable prospect of strategic partnership between Indonesia and India through bilateral economic cooperation and the feeling of pride of the remarkable progress in Indonesia. There are thirteen and five main sectors that are highlighted in the speeches. The words in general are intended to highlight and show how he felt about Indonesia that can cooperate and set up the World Economic Forum’s third country in business Forum. There were two procedures for analyzing the speech of the Indonesian President speeches. This study analyzes the content and the one of its forms. Firstly, the analysis of content had the objectives of finding the theme and the plot of the speech. The same analysis is also given access to analyze the linguistic features. The finding was also supported and cross checked by the use of the semantic analysis of the keywords of the speech as solid clues for the finding. Secondly, the analysis of the choice of form applies selectively Leech and Short’ framework (1984) in the form of linguistics categories He uses many types of the linguistic features, first, lexical categories in which mostly he uses content words such as noun or noun phrases; verbs in the form of illocutionary acts of commissive, expressive, and assertive that convince his audience and fellow citizens that the condition of Indonesia and India enhance cooperation in Business. Also, it is found the use of attributive and predicative adjectives and adverbs. Secondly, to better activate his audience’s interest more compound and complex sentences are used. It is grammatical categories; in the speech it shows how the use of compound and complex sentences comprise good coherence. Thirdly, the figures of speech used are metaphor, and very few in the forms of personification and anaphora. The uses of figures of speech help unify ideas for the speeches. The forth is cohesive devices; the cohesion in speech is achieved by the use of cohesive devices such as co-reference pronouns, conjunctions and word repetition throughout the speech. Key words: theme, plot structure, linguistics categories, illocutionary, cohesive devises